Devir-criança da Matemática: Experimentações em uma pesquisa com imagens e infâncias - Chisté, Bianca Santos [UNESP]; Leite, César Donizetti Pereira [UNESP]; De Oliveira, Luana Priscila [UNESP] (FapUNIFESP (SciELO), 2015)
This article is presented for the purpose of reflecting on the child, childhood education and mathematics education. We depart from a research developed in a Public Early Childhood School in Vilhena-RO, using the images of children production methodology. The study raises the following question: What can an imaging of research production of small children provoke mathematics, mathematics education, and research in mathematics education to think? In this way, we seek to discuss the research and its relation to the experience, as a way to test ourselves, the inventions, the senses experimentation, feelings, and knowledge. We believe that the research shows an important discussion for mathematics education: that may be more watchful, which is distinguished by an attitude to the multiple dimensions of learning and that is configured in a movement of reciprocal and inseparable invention of self-mathematics and the world.
Becoming-child of Mathematic: Experimentations in a research of images and childhood
Keywords: Becoming-child of Mathematics; Childhood; Experience; Images; Research